Nonlinear dynamic modeling and optimal motion analysis of two-link manipulators - Moein Taheri (Institute of Advanced Engineering and Science, 2016)
Manipulators are used in various industrial applications to perform variant operations such as conveying payloads. Regarding to their applications, dynamic modeling and motion analysis of manipulators are known as important and appealing tasks. In this work, nonlinear dynamics and optimal motion analysis of two-link manipulators are investigated. To dynamic modeling of the system, the Lagrange principle is employed and nonlinear dynamic equations of the manipulator are presented in state-space form. Then, optimal motion analysis of the nonlinear system is developed based on optimal control theory. By means of optimal control theory, indirect solution of problem results in a two-point boundary value problem which can be solved numerically. Finally, in order to demonstrate the power and efficiency of method, a number of simulations are performed for a two-link manipulator which show applicability of proposed method.